Venture capital industry in Finland: Country report for the venture fun project - Terttu Luukkonen (The Research Institute of the Finnish Economy (ETLA), 2006)
This report is a descriptive account of the major features of the Venture Capital (VC) Industry in Finland. It has been prepared as a background report for a project entitled Venture Fun, carried out in an EU Network of Excellence PRIME and funded from the Sixth Framework Programme. The report provides a brief overview of the evolution and present structures of the VC industry in Finland, and draws attention to factors that affect the development of VC industry, among others, to the nature of policies pursued in this field. One of its observations is the fact that the primary rationale for policies has been closing the early phase funding gap for start-ups, the promotion of SMEs, regional development or other socio-economic objectives, rather than the promotion of VC industry. As a result, policy measures have tended to be permanent, not temporary, since the objectives are difficult to achieve in a fixed time period. Furthermore, the policies pursued have made a separation of the monetary and nonmonetary value-adding functions of VC, and only recently have acknowledged the value of the latter for the growth of high-tech start-ups.
Keywords: O16; O38; 330; Venture Capital; Start-ups; Venture Capital –directed policy; Innovation Policy; Risikokapital; Unternehmensgründung; Staatliche Einflussnahme; Innovationspolitik; Finnland